Sexual size dimorphism requires a corresponding sex difference in development time: a meta‐analysis in insects. (15th October 2013) - Teder, Tiit; Blanckenhorn, Wolf
Summary The degree and direction of sexual size dimorphism (SSD) vary greatly between animal species. At the ontogenetic level, SSD may result from sex differences in birth size, growth rate and/or development time. Nevertheless, evidence concerning proximate causation of SSD is scattered, and the data used to infer ontogenetic determinants of SSD have not always been appropriate for this purpose. I use a comprehensive literature‐derived data base of relevant sex‐specific traits on 169 species to address the significance of sex differences in larval development time (SDTD) as a proximate source of SSD in insects. In a clear majority of species (79%), SSD and SDTD were qualitatively congruent, that is, the larger sex had also a longer larval development. In strongly size‐dimorphic species, the qualitative correspondence between SSD and SDTD was nearly universal. Consistently, in a phylogenetically diverse array of insect clades, SDTD increased with increasing SSD across species. The results indicate that the evolution and maintenance of high SSD values are rarely possible without a prolonged development of the larger sex. The role of sex differences in growth rate as the ontogenetic determinant of SSD in insects requires further studies that should ideally be based on detailed monitoring of larval growth schedules. The increase in SDTD with increasing SSD is consistent with the idea that the widespread phenomenon of protandry (the emergence of male adults before females) may not be selected for per se, but rather may primarily be an incidental by‐product of other selection pressures.